Türk sermaye piyasası hukukuna göre halka açık anonim ortaklıklarda genel kurul - Dal, Seniha (My University, 2007)
TEZ ÖZETİ TÜRK SERMAYE PİYASASI HUKUKUNA GÖRE HALKA AÇIK ANONİM ORTAKLIKLARDA GENEL KURUL Anonim ortaklıkların temel amacı sermayenin tabana yaygınlaştırılması yoluyla ülke ekonomisinin kalkınmasını sağlayarak ekonomik hayatta sosyal adaletin gerçekleştirilmesidir. Ülkemizde halkın tasarruflarının yatırıma dönüştürülmesi fonksiyonu halka açık anonim ortaklıklar tarafından yerine getirilmektedir. Kapalı anonim ortaklıklar böyle bir fonksiyon icra etmeye elverişli nitelikte değildir. Bu noktadan hareketle, “Türk Sermaye Piyasası Hukukuna Göre Halka açık anonim ortaklıklarda Genel Kurul” adlı çalışmamızın birinci bölümünü Halka açık anonim ortaklıklara ayırmış bulunmaktayız. Çalışmamızın birinci bölümünde, Sermaye Piyasası Kanunu hükümlerine göre halka açık anonim ortaklıkların tanımı, hukuki tipi, türleri ve özellikleri ele alınarak bu ortaklıkların tabi oldukları yükümlülükler ile birlikte onlara tanınan olanaklara da yer verilmiş bulunmaktayız. Çalışmamızın ikinci bölümünde genel kurul kavramı ele alınarak genel kurulun organ niteliği, organ olarak sorumluluğu, toplantı türleri açıklandıktan sonra, genel kurula hakim ilkelerle birlikte halka açık anonim ortaklıklarda genel kurulun yönetim kuruluna devredilen yetkileri incelenerek genel kurul toplantısına, toplantı ve karar yetersayılarına ilişkin düzenlemeler ele alınmıştır. Çalışmamızın üçüncü bölümünde ise, özellikle halka açık anonim ortaklıklarda küçük tasarrufları olan çok sayıda pay sahiplerinin genel kurul toplantılarına katılmamaları sonucu ortaklık yönetimi başkalarının eline geçtiğinden, ortaklıkta meydana gelen “güç boşluğu” sorununu gidermeye yönelik sermaye piyasası mevzuatındaki şu düzenlemelere yer verilmiştir: vekaleten oy kullanma, çağrıda bulunarak vekalet toplanması, çağrı yoluyla hisse senedi toplanması, birikimli oy kullanma, oydan yoksun hisse senetleri ve azınlık haklarının korunması. Ayrıca, Sermaye Piyasası Kurulunun düzenlediği kurumsal yönetim ilkeleri ile birlikte Türk Ticaret Kanunu Tasarısı’nda “güç boşluğu” sorununu gidermeye yönelik düzenlemelere de kısaca değinilmiştir.

GENERAL SHAREHOLDERS’ MEETING IN PUBLICLY-HELD JOINT STOCK CORPORATIONS WITHIN THE FRAMEWORK OF TURKISH CAPITAL MARKETS LAW The main objective of the joint stock corporations is the realisation of the social justice in the economic life by providing the development of the economy of the country through spreading the capital to the masses. The function of the turning of savings into investment is fulfilled by the publicly-held joint stock corporations in our country. The closely-held corporations are not convenient to exercise such a function. At this point, the first part of our study entitled as “General Shareholders’ Meeting in Publicly-Held Joint Stock Corporations within the Framework of Turkish Capital Markets Law” is about the publicly-held joint stock corporations. The first part deals with the definition of the publicly-held joint stock corporations, their legal types, and characteristics within the framework of the provisions of the capital market law and evaluates the responsibilities of and the opportunities provided to those corporations. The second part of our study starts with the concept of the general shareholders’ meeting and explains the body characteristics of the general shareholders’ meeting, its responsibility as a body and types of meetings. Then it evaluates the authorities of the general shareholders’ meeting in publicly-held joint stock corporations, which are transferred to the board of management, as well as the dominant principles of the general shareholders’ meeting. It also deals with the regulations about general shareholders’ meeting and the quorum for that meeting to be held and decisions to be taken. The third part of our study deals with the following regulations: proxy, proxy contest, tender-offer, cumulative voting, nonvoting shares, protection of minority rights. Those regulations are found in the capital market regulations, which are designed to solve the problem of the separation of ownership and control in the partnership. This problem can be seen in the transfer of the management of the partnership to the others, which is especially because of the non-participation of the many shareholders with small savings to the general shareholders’ meeting in the publicly-held joint stock corporations. Moreover, this part briefly explains the corporate governance principles regulated by the capital markets board and the regulations of the draft of the Turkish Commercial Code, designed to solve the problem of the separation of ownership and control.
Keywords: Hukuk_Sermaye Piyasası; Özel Hukuk; Sermaye Piyasası_Türkiye